The importance of ‘tooglies’ to the ethnography of F.E. Williams, government anthropologist - Rohatynskyj, Marta (The Australian journal of anthropology, 2017)
The theoretical orientation, encapsulated in the semi-serious concept of ‘tooglies'of F.E. Williams, government anthropologist for the Territory of Papua in the inter-war period, is considered. His ideas about culture change are contrasted with those of Bronislaw Malinowski, who acted as his mentor at one time. His treatment of the social organisational anomaly of Sogeri Koiari ‘sex affiliation’, often cited as a case of parallel bilineal descent, is compared with Margaret Mead's analysis of the ‘Mundugumor ropes’, which is classed as the opposite, cross-sex bilineal descent. It is shown that Williams was able to get a clearer insight into this anomalous data than Mead and Fortune, and, on the whole, worked with an understanding of culture and Papuan social organisation that presages the relational approach of today.